Antiarrhythmic Drug Therapy for Maintaining Sinus Rhythm Early after Pulmonary Vein Ablation in Patients with Symptomatic Atrial Fibrillation. Issue 1 (February 2014) - Sohns, Christian; von, Valerie; Sossalla, Samuel; Bergau, Leonard; Seegers, Joachim; Lüthje, Lars; Vollmann, Dirk; Zabel, Markus
Summary Aims The optimal pharmacological treatment for patients early after ablation of atrial fibrillation (AF) is still not clear. We analyzed if concomitant antiarrhythmic drug (AAD) therapy significantly alters early recurrence of AF/atrial tachycardia (AT) following pulmonary vein ablation (PVA). Methods For the first 2 months after PVA, 274 patients (age 62 ± 10 years; 66% male) were individually scheduled for concomitant treatment with beta‐adrenergic blocking agents (BB) or AAD therapy. Primary endpoint of this study was a composite of (1) AF/AT lasting more than 30 seconds; (2) symptomatic AF/AT recurrence requiring intervention; or (3) intolerance to the antiarrhythmic agent given. Univariate and multivariate analysis was performed to evaluate predictors for successful AAD therapy. Results Early after PVA, patients were treated with BB (n = 89), flecainide (n = 99), sotalol (n = 37), dronedarone (n = 29), or amiodarone (n = 115). Ninety‐five patients received a combination of AAD therapy and BB. A total of 369 observation periods were analyzed. Over the first 2 months following PVA, AF/AT recurrences were found in 42% of patients. No significant difference regarding freedom from AF/AT recurrence with regard to different drug therapies was observed (P = 0.769). In multivariate analysis, none of the parameters were significant to predict success of AAD therapy. In nine observations, AAD therapy was terminated due to side effects presumably related to the respective agent. Conclusions Following PVA, AAD therapy is not superior to BB treatment for the prevention of early atrial arrhythmias. Furthermore and confirmed by multivariate analysis, no drug was superior to another regarding the maintenance of sinus rhythm.